Silicon carbide ion beam polishing optimization method based on light metal ion doped quantum dots

By growing the sacrificial layer doped with quantum dots in situ on the surface of SiC materials and using pulse ion beam polishing technology, the problem of difficult to achieve high-precision processing in traditional polishing processes is solved, and the high flatness and finish of the surface of SiC materials is achieved.

CN119811980AActive Publication Date: 2025-04-11CHANGCHUN UNIV OF SCI & TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411726662.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Traditional chemical polishing processes are difficult to meet the requirements of high-precision processing of SiC materials, which can easily lead to microscopic defects, scratches or damage on the surface, affecting the performance and reliability of the device.

Method used

The silicon carbide ion beam polishing method based on light metal ion doped quantum dots is used to optimize the polishing parameters to achieve higher flatness and finish by growing the CsPbBr3 quantum dot sacrificial layer in situ on the surface of SiC materials and performing pulsed ion beam polishing in an Ar atmosphere.

Benefits of technology

The flatness and finish of the surface of SiC materials are improved, surface defects and traps are reduced, and the interface bonding between the quantum dot layer and the SiC wafer is enhanced, achieving efficient and fine surface smoothing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811980A_ABST
    Figure CN119811980A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbide ion beam polishing optimization method based on light metal ion doped quantum dots, and belongs to the technical field of sacrificial layer materials. The method for in-situ growth of the CsPbBr3 quantum dot sacrificial layer on the surface of the SiC material comprises the following steps: mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution; light metal ions are doped in the CsPbBr3 precursor solution, and a CsPbBr3 precursor solution doped with the light metal ions is obtained; and dropwise adding the light metal ion doped CsPbBr3 precursor solution to the surface of the SiC material, flattening, heating for crystallization, and annealing to obtain the SiC material with the CsPbBr3 quantum dot sacrificial layer grown in situ. According to the invention, the CsPbBr3 quantum dot layer is used as a sacrificial layer of the SiC wafer, the light-emitting performance of the quantum dots is improved through light metal ion doping, and meanwhile, the interface bonding force between the quantum dot layer and the SiC wafer is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sacrificial layer materials, and in particular to a method for optimizing silicon carbide ion beam polishing based on light metal ion-doped quantum dots. Background Art

[0002] Silicon carbide (SiC), as an advanced material with excellent performance, has been widely used in many fields due to its excellent mechanical strength, high temperature stability, chemical inertness and wide bandgap semiconductor properties. Especially in semiconductor and optoelectronic devices, SiC has become an important basic material for the next generation of electronic and optoelectronic technologies because it can maintain stable performance under high pressure, high temperature and extreme environments. However, it is precisely because of the high hardness and strong chemical inertness of SiC materials that traditional chemical polishing processes are difficult to meet the requirements of high-precision processing. Existing SiC materials often have problems such as low processing efficiency, long time, and poor surface quality during the chemical polishing process, which can easily lead to surface microscopic defects, scratches or damage, thereby affecting the overall performance and reliability of the device. With the continuous improvement of the surface quality requirements of SiC materials, the limitations of traditional polishing technology in high-precision processing have become increasingly prominent.

[0003] Ion beam polishing can remove and modify the microstructure of SiC surface by utilizing the physical and chemical properties of high-energy ion beams, achieving highly precise material surface processing. Unlike traditional mechanical polishing, the ion beam polishing process does not require direct contact with the material surface, thus avoiding damage caused by mechanical stress and improving the uniformity and surface finish of the polishing. In addition, ion beam polishing exhibits excellent uniformity when processing high-hardness materials, significantly improving the surface finish and overall processing quality.

[0004] Although ion beam polishing technology has great processing potential, there are still some technical challenges in practical applications. A key issue is that during the polishing process, due to the different ion beam polishing rates, there are also differences in material removal rates, which can easily lead to changes in the roughness of the SiC surface material layer. Different ion beam parameters (such as energy, angle, etc.) may lead to inconsistent removal rates of surface atomic layers, thereby affecting the final flatness and finish of the surface. In some cases, excessive erosion or uneven action of the ion beam can also cause the formation of irregular surface features or microscopic defects, weakening the processing effect, and still needs further improvement. Summary of the invention

[0005] The purpose of the present invention is to provide a method for optimizing ion beam polishing of silicon carbide based on light metal ion doped quantum dots to solve the above-mentioned problems in the background technology. The present invention selects CsPbBr3 quantum dot composite film as the sacrificial layer of SiC material, mainly because the unique advantages of the prepared CsPbBr3 quantum dot sacrificial layer in terms of size, fluorescence efficiency and coupling with the substrate have been discovered. The present invention first uses the quantum dot layer as the sacrificial layer of the SiC wafer, improves the luminescence performance of its quantum dots by doping with light metal ions, and enhances the interface bonding force between the quantum dot layer and the SiC wafer, thereby ensuring that it obtains a silicon carbide material with higher flatness and smoothness during ion beam polishing, while avoiding the problem of surface irregularities or microscopic defects caused by excessive erosion or uneven action of the ion beam on silicon carbide.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for in-situ growing a CsPbBr3 quantum dot sacrificial layer on a SiC material surface, comprising the following steps:

[0008] (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution;

[0009] (2) doping the CsPbBr3 precursor solution with light metal ions to obtain a light metal ion-doped CsPbBr3 precursor solution;

[0010] (3) adding the light metal ion-doped CsPbBr3 precursor solution dropwise to the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer.

[0011] Preferably, the lead source is PbBr2; the cesium source is CsBr; and the molar ratio of the lead source to the cesium source is 0.9-1.1.

[0012] Preferably, the solvent is polymethyl methacrylate and / or N,N-dimethylformamide.

[0013] Preferably, the type of light metal ion is Na + or K + ; The molar ratio of the lead source to the light metal ion is 64-6400:1.

[0014] Preferably, the temperature of the crystallization is 70-100°C and the time is 1-2 minutes.

[0015] Preferably, the annealing temperature is 70-110° C. and the time is 1-5 min.

[0016] The second technical solution of the present invention is to provide a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer prepared according to the above method.

[0017] Technical solution three of the present invention: Provide a polishing method for the SiC material having a CsPbBr3 quantum dot sacrificial layer grown in situ, comprising the following steps:

[0018] In an Ar gas atmosphere, the SiC material having the in-situ grown CsPbBr3 quantum dot sacrificial layer is subjected to pulsed ion beam polishing to obtain a polished SiC material.

[0019] Preferably, the parameters of the pulsed ion beam polishing are: ion beam power 110W, pulse frequency 100Hz, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow 20SCCM, and polishing time 1-2min.

[0020] Under the pulse ion beam polishing parameters defined in the present invention, a polishing rate of 0.17 μm / min can be achieved.

[0021] Technical solution four of the present invention: provides an optimization method for silicon carbide ion beam polishing, in situ growing a CsPbBr3 quantum dot sacrificial layer on the silicon carbide surface, and then performing pulsed ion beam polishing.

[0022] The technical principles of the present invention are as follows:

[0023] Pulsed ion beam polishing stage: The present invention places the SiC material with the in-situ grown CsPbBr3 quantum dot sacrificial layer on the ion beam etcher, firstly introduces argon (Ar) into the etching chamber, ionizes it through the ion source to generate argon ions, and forms a high-density plasma; then accelerates and focuses the ion beam through the three-grid ion optical system, so that the ion beam can act accurately on the wafer surface; then, the accelerating electric field is used to excite the ion beam to remove the sacrificial layer on the wafer surface. In each pulse cycle, the Ar in the plasma +Under the action of the accelerating electric field, the wafer surface is impacted with a specific energy to remove the material at the atomic level. By adjusting the rate of the plasma beam, the thickness of the material removed can be accurately controlled during each pulse, making the material removal process more uniform. The pulse ion beam frequency is selected to be 100Hz. When the pulse frequency is lower than 100Hz, the effect of ions on the material surface is relatively mild, which will result in a longer processing time and waste of manpower and material resources. When the pulse frequency is higher than 100Hz, the temperature of the material surface will rise faster, resulting in increased local melting and evaporation of the material, thereby causing heat loss on the material surface and increasing the surface roughness. Therefore, the optimized ion beam pulse setting can effectively reduce the impact on the SiC wafer surface, avoid introducing new surface damage, and achieve smooth removal of the sacrificial layer.

[0024] The purpose of the annealing treatment defined in the present invention is to promote the further crystallization and growth of CsPbBr3 quantum dots. The CsPbBr3 sacrificial layer after annealing can be more firmly bonded to the silicon carbide substrate. The product that has not been annealed not only has a higher roughness, but also the sacrificial layer is more likely to fall off from the substrate. Annealing can effectively enhance the coupling strength between the quantum dot sacrificial layer and the substrate.

[0025] The beneficial technical effects of the present invention are as follows:

[0026] The present invention proposes a method for optimizing SiC ion beam polishing of light metal ion-doped quantum dots. The method aims to solve the problems in the existing ion beam polishing process, especially to improve the flatness of the polished surface. Specifically, the quantum dot layer is first used as a sacrificial layer of the SiC wafer, and the luminescence performance of the quantum dots is improved by light metal ion doping, the surface defects and traps of the sacrificial layer are reduced, and the interface bonding force between the quantum dot layer and the SiC wafer is enhanced, thereby improving the subsequent polishing quality.

[0027] In the polishing stage, the present invention adopts optimized pulsed ion beam technology to achieve efficient flattening of SiC wafers. Under the polishing parameters defined in the present invention, the etching rate of the prepared sacrificial layer is close to that of the SiC substrate material, so the smooth surface covered with the sacrificial layer can be transferred to the surface of the SiC substrate. Compared with the traditional polishing method, the present invention can quickly remove the sacrificial layer without introducing surface damage by accurately controlling the energy of the ion beam, thereby improving the optical quality and mechanical strength of the wafer surface and achieving efficient and fine surface smoothing.

[0028] The present invention selects CsPbBr3 quantum dot composite film as the sacrificial layer of SiC material, mainly because the unique advantages of the prepared CsPbBr3 quantum dot sacrificial layer in terms of size, fluorescence efficiency and coupling with the substrate are found. In order to further enhance the fluorescent labeling effect of CsPbBr3 quantum dots, the present invention adopts a light metal ion doping strategy, and significantly improves the luminescence intensity and stability of quantum dots by introducing light metal ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 Schematic diagram of the pulsed ion beam polishing process of Example 1-2.

[0031] Figure 2 The performance characterization of the SiC material with in-situ growth of CsPbBr3 quantum dot sacrificial layer in Examples 1-2 and Comparative Example 1. Among them, (a) is the PL spectrum comparison of Example 1 and Comparative Example 1, (b) is the PL spectrum comparison of Example 2 and Comparative Example 1. (c) is the absorption spectrum of Examples 1-2 and Comparative Example 1, and (d) is the XRD spectrum of Examples 1-2 and Comparative Example 1.

[0032] Figure 3 The wafer surface morphology images of the SiC materials after polishing in S3 and Comparative Example 1. Among them, (a) is the SiC material after polishing in S3, and (b) is Comparative Example 1.

[0033] Figure 4 This is a surface morphology image of the wafer of the polished SiC material of Comparative Example 2.

[0034] Figure 5 This is a wafer surface morphology image of the SiC material after polishing in Comparative Example 3.

[0035] Figure 6 This is the curve of ion beam removal thickness and wafer surface roughness variation.

[0036] Figure 7 This is the polishing rate and wafer surface roughness change curve.

[0037] Figure 8 The wafer surface morphology before and after polishing. Among them, (a) is the SiC material with in-situ growth of CsPbBr3 quantum dot sacrificial layer, and (b) is the SiC material after polishing.

[0038] Fig. 9 The wafer surface morphology of the product before and after polishing at a polishing rate of 0.22 μm / min. Among them, (a) is the SiC material with a CsPbBr3 quantum dot sacrificial layer grown in situ, and (b) is the SiC material after polishing.

[0039] Fig.10 The wafer surface morphology of the product before and after polishing at a polishing rate of 0.05 μm / min. Among them, (a) is the SiC material with a CsPbBr3 quantum dot sacrificial layer grown in situ, and (b) is the SiC material after polishing. DETAILED DESCRIPTION

[0040] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0041] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0042] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0044] The present invention discloses a method for in-situ growing a CsPbBr3 quantum dot sacrificial layer on a SiC material surface, comprising the following steps:

[0045] (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution;

[0046] (2) doping the CsPbBr3 precursor solution with light metal ions to obtain a light metal ion-doped CsPbBr3 precursor solution;

[0047] (3) adding the light metal ion-doped CsPbBr3 precursor solution dropwise to the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer.

[0048] Preferably, the step (1) is specifically:

[0049] In a nitrogen environment, 1 g of polymethyl methacrylate (PMMA) and 2-4 mL of N,N-dimethylformamide (DMF) were mixed, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 100-130° C. The speed of the magnetic stirring was adjusted to 1500-1800 rpm, and the mixture was stirred for 1-3 h until a transparent solution was formed, thereby obtaining a PMMA / DMF solution;

[0050] In a nitrogen environment, 1.267 g of PbBr2 (lead bromide) and 0.514 g of CsBr (cesium bromide) powder were taken in 40 mL glass bottles, 4-6 mL of DMF were added, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 50-80 ° C, and the speed of the magnetic stirring was adjusted to 1000-1500 rpm. Stir overnight, and then filter through a 0.22 μm syringe filter to obtain CsBr / DMF solution and PbBr2 / DMF solution respectively;

[0051] In a nitrogen environment, the CsBr / DMF solution and the PMMA / DMF solution are mixed, and a magnetic bar is put into the mixture, which is placed on a heating plate. The temperature of the heating plate is adjusted to 80-100°C, the speed of the magnetic stirring is adjusted to 1500-1800rpm, and the mixture is stirred for 10-12h to obtain an intermediate solution. The PbBr2 / DMF solution and the intermediate solution are then mixed at a PbBr2:CsBr molar ratio of 0.9-1.1, and the mixture is heated and stirred at a temperature of 80-100°C and a speed of 1500-1800rpm for 10-12h to obtain the CsPbBr3 precursor solution.

[0052] Preferably, the step (2) is specifically:

[0053] In a nitrogen environment, weigh 0.102g NaBr (sodium bromide) powder or 0.119g KBr (potassium bromide) powder into a 40mL glass bottle, add 4-6mL DMF, put in a magnetic bar, place on a heating plate, set the heating plate temperature to 50-80°C, adjust the speed of the magnetic stirring to 1000-1500rpm, stir overnight to obtain an ion-doped liquid; then mix the ion-doped liquid and the CsPbBr3 precursor solution in a volume ratio of 1:1-100 to obtain a light metal ion-doped CsPbBr3 precursor solution.

[0054] Preferably, the step (3) is specifically:

[0055] After preheating the light metal ion-doped CsPbBr3 precursor solution to 70-100°C, add it dropwise onto the cleaned SiC wafer substrate, use a coating machine to spin coat it at a speed of 1000-2000rpm for 20-40s, then place it on a heating plate at 70-100°C to promote in-situ nucleation and crystallization of CsPbBr3 quantum dots, and then anneal it at 70-110°C for 1-5min to obtain a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer (light metal ion-doped CsPbBr3 quantum dot composite film).

[0056] Unless otherwise specified, "overnight" in the present invention is calculated as 12 hours.

[0057] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0058] Example 1

[0059] A method for in-situ growth of a CsPbBr3 quantum dot sacrificial layer on a SiC material surface and a polishing method thereof, the steps are as follows:

[0060] (1) Preparation of CsPbBr3 precursor solution:

[0061] In a glove box with a nitrogen environment, 1 g of PMMA and 4 mL of DMF were mixed, and a magnetic stirrer was placed on a heating plate. The temperature of the heating plate was set to 100 °C, and the speed of the magnetic stirrer was adjusted to 1600 rpm. The mixture was stirred for 1 h until a transparent solution was formed, thereby obtaining a PMMA / DMF solution.

[0062] In a glove box under nitrogen environment, 1.267 g of PbBr2 and 0.514 g of CsBr powder were taken into 40 mL glass bottles, 5 mL of DMF was added, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 50 ° C, and the speed of the magnetic stirring was adjusted to 1300 rpm. Stir overnight, and then filter through a 0.22 μm syringe filter to obtain CsBr / DMF solution and PbBr2 / DMF solution respectively;

[0063] In a glove box in a nitrogen environment, CsBr / DMF solution and PMMA / DMF solution were mixed in a volume ratio of 3:40, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was adjusted to 90°C, the speed of the magnetic stirring was adjusted to 1600 rpm, and the stirring was performed for 10 hours to obtain an intermediate solution; then the PbBr2 / DMF solution was mixed with the intermediate solution (the molar ratio of the Pb element in the PbBr2 / DMF solution to the Cs element in the intermediate solution was 0.9, and the heating and stirring were continued at a temperature of 90°C and a speed of 1600 rpm for 10 hours to obtain a CsPbBr3 precursor solution.

[0064] (2) Preparation of light metal ion-doped CsPbBr3 precursor solution:

[0065] In a glove box with a nitrogen environment, 0.102 g of NaBr powder was weighed into a 40 mL glass bottle, 4 mL of DMF was added, and a magnet was placed on a heating plate. The temperature of the heating plate was set to 50 ° C, the speed of the magnetic stirring was adjusted to 1300 rpm, and stirred overnight to obtain a Na ion-doped solution; then the Na ion-doped solution and the CsPbBr3 precursor solution were mixed at volume ratios of 1:1, 1:2, 1:4, 1:10, 1:50, and 1:100, respectively, and ultrasonicated for 10 minutes to obtain CsPbBr3 precursor solutions doped with light metal ions with different doping ratios.

[0066] (3) Preparation of light metal ion doped CsPbBr3 quantum dot composite film:

[0067] The above-mentioned light metal ion-doped CsPbBr3 precursor solution was preheated to 80°C, and then dropped onto the cleaned SiC wafer substrate. A coating machine was used to spin coat the solution at 2000 rpm for 30 seconds, and then the solution was placed on a heating plate at 100°C for 1 minute, and then annealed at 80°C for 3 minutes to obtain SiC materials with in-situ grown CsPbBr3 quantum dot sacrificial layers (light metal ion-doped CsPbBr3 quantum dot composite films) of different doping ratios.

[0068] (4) The SiC materials with in-situ growth of CsPbBr3 quantum dot sacrificial layers at different doping ratios are polished, respectively, and the steps are as follows:

[0069] 1. Clean the finished product with an air gun to ensure that it is free of dust and other contaminants, then install the workpiece on a high-precision processing platform and ensure that its position is fixed.

[0070] 2. Set the ion beam polishing parameters: ion beam power 110W, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow 20SCCM, polishing rate 0.17μm / min. Set the scanning mode of the polishing process to rectangular coordinate mode.

[0071] 3. Start the vacuum pump to ensure that the polishing process is carried out in a high vacuum environment to avoid collision between the ion beam and air molecules and reduce energy loss.

[0072] 4. Start the ion source to generate an ion beam. The ion beam used is Ar + source.

[0073] 5. Start the polishing process and set the polishing time to 1.2 minutes.

[0074] 6. After polishing is completed, the working environment is restored to a normal state to obtain a polished SiC material (the polished SiC material when the volume ratio of the Na ion doping solution to the CsPbBr3 precursor solution is 1:10 is recorded as S1).

[0075] Example 2

[0076] The only difference from Example 1 is that the preparation method of the light metal ion-doped CsPbBr3 precursor solution is modified as follows:

[0077] In a glove box in a nitrogen environment, 0.119 g of KBr powder was weighed into a 40 mL glass bottle, 4 mL of DMF was added, and a magnet was placed on a heating plate. The temperature of the heating plate was set to 50°C, the speed of the magnetic stirring was adjusted to 1300 rpm, and the mixture was stirred overnight to obtain a K ion-doped solution; then the K ion-doped solution and the CsPbBr3 precursor solution were mixed at volume ratios of 1:1, 1:2, 1:4, 1:10, 1:50, and 1:100, respectively, and ultrasonicated for 10 minutes to obtain CsPbBr3 precursor solutions doped with light metal ions at different doping ratios (the polished SiC material when the volume ratio of the final K ion-doped solution to the CsPbBr3 precursor solution was 1:50 was recorded as S2, and the SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer when the volume ratio of the final K ion-doped solution to the CsPbBr3 precursor solution was 1:100 was recorded as S3).

[0078] Figure 1 Schematic diagram of the pulsed ion beam polishing process of Example 1-2.

[0079] Comparative Example 1

[0080] The only difference from Example 1 is that step (2) is omitted, and the CsPbBr3 precursor solution in step (1) is directly preheated and subsequently treated.

[0081] Comparative Example 2

[0082] The only difference from S3 is that the pulse frequency is changed to 150Hz.

[0083] Comparative Example 3

[0084] The only difference from S3 is that the operation of annealing at 80° C. for 3 min is omitted.

[0085] Effect verification

[0086] 1. The photoluminescence performance of the SiC material with in-situ growth of CsPbBr3 quantum dot sacrificial layer in Examples 1-2 and Comparative Example 1 was characterized. The test results are as follows: Figure 2 shown.

[0087] Figure 2 The performance characterization of the SiC material with in-situ growth of CsPbBr3 quantum dot sacrificial layer in Examples 1-2 and Comparative Example 1. Among them, (a) is the PL spectrum comparison of Example 1 and Comparative Example 1, (b) is the PL spectrum comparison of Example 2 and Comparative Example 1. (c) is the absorption spectrum of Examples 1-2 and Comparative Example 1, and (d) is the XRD spectrum of Examples 1-2 and Comparative Example 1.

[0088] Figure 2 In (a) and (b), the curve labeled 0 represents comparative example 1, and the curves labeled 1:1, 1:2, 1:4, 1:10, 1:50, and 1:100 respectively represent the SiC material with in-situ grown CsPbBr3 quantum dot sacrificial layer obtained at the corresponding ion doping liquid concentrations in the corresponding embodiments.

[0089] Figure 2 In (c) and (d), Na doped represents the material data when the volume ratio of Na ion doping solution to CsPbBr3 precursor solution is 1:10, K doped represents the material data when the volume ratio of K ion doping solution to CsPbBr3 precursor solution is 1:50, and W / O and no doped represent the product data of Comparative Example 1.

[0090] Depend on Figure 2 It can be seen that the photoluminescence spectrum (PL) peak of the material is at 519nm. As the concentration of light metal ions increases, the PL of the CsPbBr3 quantum dots in the material will have a slight red shift, indicating a decrease in the band gap. +When the doping ratio is 1:10, the PL peak of CsPbBr3 quantum dots is the highest, which is 2.9 times higher than that of the undoped sample (Comparative Example 1). + When the ion doping ratio is 1:50, the PL peak of CsPbBr3 quantum dots is the highest, which is 2.5 times higher than that of undoped samples. Therefore, light metal doping has an improving effect on the luminescence intensity of CsPbBr3 quantum dots. This may be because the doping of light metal ions can effectively passivate the defects and traps on the surface of the CsPbBr3 quantum dot film, thereby reducing the defects and traps on the surface of the film. However, when the doping ratio of light metal monovalent cations increases, it will cause fluorescence quenching of CsPbBr3 quantum dots; when the doping concentration is 1:1, the fluorescence effect of CsPbBr3 quantum dots is completely quenched. This may be because the increase in the concentration of doping ions will lead to an increase in non-radiative recombination centers in CsPbBr3 quantum dots or the generation of deep energy level defects, thereby reducing the luminescence brightness of CsPbBr3 quantum dots. Figure 2 From (c) in Figure 1, we can see that the doping of light metal ions has no significant effect on the absorption spectrum, and the absorption band is at 525nm. Figure 2 As shown in (d), the main crystal planes (100), (110), (200), (210), (220), and (300) of CsPbBr3 quantum dots were detected in all materials, proving that light metal doping did not change the crystal structure of CsPbBr3 quantum dots. + The XRD characteristic peaks of doped CsPbBr3 are sharper, indicating that it has higher crystallinity after doping.

[0091] 2. In order to characterize the surface roughness of the wafer after ion beam polishing, a white light interferometer was used to characterize the surface roughness of the polished SiC material in Examples 1-2 and Comparative Example 1 to evaluate the polishing effect. The characterization method is as follows:

[0092] (1) Clean the polished SiC material surface to prevent oil, fingerprints or other contaminants from affecting the measurement results.

[0093] (2) A Zygo NewView 700s white light interferometer was used to perform micrometer-scale medium and high frequency detection on the wafer surface. A magnification of 50 times was selected, the detection range was 468μm×351μm, and the maximum resolution was 1024×1024 pixels.

[0094] (3) Place the SiC wafer on the interferometer measurement table and adjust the optical focal length until the workpiece surface is clearly visible.

[0095] (4) Randomly test two points on the SiC wafer, calculate the surface roughness parameters and reconstruct the three-dimensional surface shape.

[0096] By controlling the ion beam pulse frequency, the thickness of the sacrificial layer removed by the ion beam in S3 (0-300nm) is controlled, and the corresponding wafer surface roughness is calculated. The test results are as follows Figure 6 shown.

[0097] By controlling the polishing rate, the effect on the surface roughness of the wafer is statistically analyzed. The test results are as follows: Figure 7 shown.

[0098] Figure 6 The ion beam removal sacrificial layer thickness and wafer surface roughness change curve of S3 and the wafer surface morphology. Among them, (a) is the wafer surface roughness change curve, (b) and (c) are the wafer surface morphology at different removal thicknesses.

[0099] Figure 7 This is the polishing rate and wafer surface roughness variation curve of S3.

[0100] Figure 8 The wafer surface morphology of S3 before and after polishing. Among them, (a) is S3, and (b) is the SiC material after polishing.

[0101] The polishing rate of S3 is controlled by controlling the ion beam power (when the power is 200W, the polishing rate is 0.22μm / min; when the power is 50W, the polishing rate is 0.05μm / min), and the corresponding wafer surface roughness is calculated. The test results are as follows: Figure 9-10 shown.

[0102] Fig. 9 This is the wafer surface morphology of the product of S3 at a polishing rate of 0.22μm / min before and after polishing.

[0103] Among them, (a) is S3, and (b) is the polished SiC material.

[0104] Fig.10 The wafer surface morphology of the product of S3 at a polishing rate of 0.05 μm / min before and after polishing. Among them, (a) is S3, and (b) is the SiC material after polishing.

[0105] Figure 6 The roughness change of the wafer surface under different removal thicknesses is shown. The change in surface roughness is divided into two parts. In the first part, the roughness increases rapidly because the ion beam deposits more energy at the notch when removing the sacrificial layer of the material. In the second part, as the thickness of the ion beam polishing increases, the notch depth gradually decreases and the roughness decreases. Therefore, the thickness of the sacrificial layer of the material cannot be too thin, otherwise it will lead to incomplete defect filling, which will increase the surface roughness. If the sacrificial layer of the material is too thick, it will increase the polishing time and waste financial and material resources. By optimizing the thickness of the quantum dot sacrificial layer, the thickness is determined to be 200nm.

[0106] Depend on Figure 7 It can be seen that at a polishing rate of 0.17 μm / min, the roughness of the wafer is the lowest, which is 1.568 nm ( Figure 8 ), the roughness of the SiC wafer is effectively reduced by nearly half compared to before polishing. When the polishing rate is greater than 0.17μm / min (0.22μm / min), the ion beam bombards the wafer surface unevenly, and the surface defects of the wafer are not effectively removed, and the roughness increases ( Fig. 9 When the polishing rate is less than 0.17μm / min (0.05μm / min), the material removal rate will be significantly reduced ( Fig.10 ), resulting in the entire polishing process taking longer, which is particularly disadvantageous in mass production and will increase production cycles and operating costs; long-term slow processing will also cause the surface temperature to gradually increase. Although the energy input of the pulsed ion beam itself is low, continuous processing may still cause temperature accumulation and cause thermal stress, thereby affecting the temperature flatness of the surface and increasing its surface roughness.

[0107] Figure 3 The wafer surface morphology images of the SiC materials after polishing in S3 and Comparative Example 1. Among them, (a) is the SiC material after polishing in S3, and (b) is Comparative Example 1.

[0108] like Figure 3 As shown, the surface roughness of the silicon carbide coated with a sacrificial layer doped with light metal ions after polishing is 1.568nm (S3), and the surface roughness of the silicon carbide coated with a sacrificial layer not doped with light metal ions after polishing is 2.947nm (Comparative Example 1), and the surface roughness is increased by nearly 2 times.

[0109] Figure 4 This is a surface morphology image of the wafer of the polished SiC material of Comparative Example 2.

[0110] like Figure 4 As shown, Figure 3 As shown, the roughness of the product of Comparative Example 2 is 9.649 nm, which is 9 times higher than that of the product (S3) prepared at 100 Hz.

[0111] Figure 5 This is a wafer surface morphology image of the SiC material after polishing in Comparative Example 3.

[0112] like Figure 5 As shown, the product without annealing treatment (Comparative Example 3) has a higher roughness, which is increased by about 2700%.

[0113] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for in-situ growth of a CsPbBr3 quantum dot sacrificial layer on a SiC material surface, characterized in that: The following steps are involved: (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution; (2) doping the CsPbBr3 precursor solution with light metal ions to obtain a light metal ion-doped CsPbBr3 precursor solution; (3) adding the light metal ion-doped CsPbBr3 precursor solution dropwise to the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer.

2. The method according to claim 1, characterized in that The lead source is PbBr2; the cesium source is CsBr; and the molar ratio of the lead source to the cesium source is 0.9-1.

1.

3. The method according to claim 1, characterized in that The solvent is polymethyl methacrylate and / or N,N-dimethylformamide.

4. The method according to claim 1, characterized in that: The type of light metal ion is Na + or K + .

5. The method according to claim 1, characterized in that The temperature of the temperature-raising crystallization is 70-100° C., and the time is 1-2 minutes.

6. The method according to claim 1, characterized in that The annealing temperature is 70-110° C. and the annealing time is 1-5 min.

7. A SiC material having an in-situ grown CsPbBr3 quantum dot sacrificial layer prepared according to the method of any one of claims 1 to 6.

8. A polishing method for SiC material with in-situ growth of CsPbBr3 quantum dot sacrificial layer as claimed in claim 7, characterized in that: The following steps are involved: In an Ar gas atmosphere, the SiC material having the in-situ grown CsPbBr3 quantum dot sacrificial layer is subjected to pulsed ion beam polishing to obtain a polished SiC material.

9. The method according to claim 8, characterized in that The parameters of the pulsed ion beam polishing are: ion beam power 110W, pulse frequency 100Hz, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow rate 20SCCM, and polishing time 1-2min.

10. A method for optimizing silicon carbide ion beam polishing, characterized in that: A CsPbBr3 quantum dot sacrificial layer is in-situ grown on the silicon carbide surface and then pulsed ion beam polishing is performed.

Citation Information

Patent Citations

  • Blue light CsPbBr3 perovskite thin film and preparation method thereof

    CN118302008A

  • Self-standing perovskite oxide thin film, and preparation method therefor and use thereof

    WO2024103780A1